Mapping of DTPA-Extractable Cationic Micronutrients in Soils under Rice and Maize Ecosystems of Kupwara District in Kashmir – A GIS Approach - and Shaista N., Mushtaq A. Wani, Zahid M. Wani, M.A. Bhat, N.A. Kirmani (Journal of the Indian Society of Soil Science, 2015)
Mapping of DTPA-extractable cationic micronutrients were carried out by random grid sampling. Geo-referenced surface (0.2 m) soil samples representing different soils (as per soil map prepared on 1:50,000 scale) were collected from 625 sites in Kupwara district (Northwest Kashmir) using global positioning system (GPS) before the crops sown. The plant samples were also collected simultaneously from every 5th soil sampling site. These soil and plant samples were analyzed for micronutrients (Fe, Mn, Zn and Cu). The DTPA-Zn in soils varied from 0.12 to 5.10 mg kg-1, DTPA-Cu from 0.26 to 3.90 mg kg-1, DTPA-Fe from 0.89 to 51.18 mg kg-1 and DTPA-Mn from 0.51 to 33.30 mg kg-1. The contents of Zn in plants varied from 16.3 to 73.7 mg kg-1, Fe from 22.4 to 585.0 mg kg-1, Cu from 7.6 to 20.1 mg kg-1 and Mn from 7.3 to 649.3 mg kg-1. None of the samples were found to be deficient in Fe. The relationship between micronutrient contents in soil and plant was significant. There is a need to refine the critical level of deficiency for DTPA-Fe with reference to growing environment, certain soil characteristics and pre-defined plant parts of specific crops. Soil micronutrient maps prepared in Arc Info GIS clearly delineated the specific locales where micronutrient problem constrained crop production. Multi-micronutrient map suggested that deficiency of individual element is more prevalent as compared to that of two or three micronutrients. The DTPA extractable micronutrients showed positive correlation with organic carbon and clay. The positive influence of organic carbon on micronutrient availability was maximum for DTPA-Cu. These results indicated that Zn is likely to constraint crop production, followed by Mn in the soils of Kupwara district.